Atomic weights of the elements 2011 (IUPAC Technical Report) - Wieser, Michael E.; Holden, Norman; Coplen, Tyler B.; Bohlke, John K.; Berglund, Michael; Brand, Willi A.; De Bievre, Paul; Groning, Manfred; Loss, Robert; Meija, Juris; Hirata, Takafumi; Prohaska, Thomas; et al. (International Union of Pure and Applied Chemistry, 2013)
The biennial review of atomic-weight determinations and other cognate data has resulted in changes for the standard atomic weights of five elements. The atomic weight of bromine has changed from 79.904(1) to the interval [79.901, 79.907], germanium from 72.63(1) to 72.630(8), indium from 114.818(3) to 114.818(1), magnesium from 24.3050(6) to the interval [24.304, 24.307], and mercury from 200.59(2) to 200.592(3). For bromine and magnesium, assignment of intervals for the new standard atomic weights reflects the common occurrence of variations in the atomic weights of those elements in normal terrestrial materials.